Enhancement of cannabidiol oral bioavailability through the development of nanostructured lipid carriers: In vitro and in vivo evaluation studies - Iman E. Taha; Mahmoud A. ElSohly; Mohamed M. Radwan; Rasha M. Elkanayati; Amira Wanas; Poorva H. Joshi; Eman A. Ashour (Drug Delivery and Translational Research, 2025)
Cannabidiol (CBD) is a natural product isolated from the Cannabis sativa plant that was approved by the United States Food and Drug Administration (US FDA) for the treatment of resistant epilepsy. Despite its therapeutic potential, CBD’s clinical application is limited by its poor aqueous solubility and low oral bioavailability. The primary aim of this research was to enhance the aqueous solubility and oral bioavailability of CBD by developing nanostructured lipid carriers (NLCs) using conventional hot homogenization method (CHH). In the current study, nine CBD NLC formulations were developed through CHH, of which, NLC5 emerged as the most promising formulation, exhibiting high CBD entrapment efficiency (99.23%), particle size of 207 nm, a polydispersity index of 0.19, and a zeta potential of -26 mV. Additionally, drug release testing for NLC5 showed a high CBD release rate of more than 90% within 15 min, indicating an enhancement of CBD dissolving rate compared to pure CBD. The in vivo pharmacokinetic study of NLC5 formulation showed 27% CBD oral bioavailability. Furthermore, Stability studies conducted at 4 °C and 25 °C on this formulation over three months, revealed consistent parameters, underscoring the robustness of the formulation. In conclusion, the successful formulation of CBD-loaded NLCs resulted in improved CBD release rate, enhanced oral bioavailability of CBD, and maintained stability, making it a promising approach for the effective delivery of CBD. Graphical Abstract